Efektivitas Diet Nasi terhadap Asupan Makanan dan Lama Hari Rawat Pasien Thyphoid di RSUD Sunan Kalijaga Demak - Azizah, Nur; Rahmawati, Ana Yuliah (JURNAL RISET GIZI, 2014)
Background : Typhoid is one of the infection diseases that causes the increasing of nutrition need. However, in fact, there are still many patients who get soft diet/ porridge that will reduce feed intake.Objective : This study aims to determine the effect of rice on diet (energy, protein, fat and carbohidrat) intake and care typhoid patients.Method : This research study is an experimental Pre Static Group Comparison. Sampling was non-randomized purposive sampling.The number of sample was 34 typhoid patients. The treatment group was given rice diet and control group was given soft diet/ porridge, intake (energy, protein, fat and carbohidrat) observed comstok method. The duration of treatment was collected from data. Statistic test that was used was independent - t test if the data are normally distributed and Maan - Whitney test if the data are not normally distriuted.Results : Giving rice diet will increase energy, protein, fat, carbohydrates typhoid patients was10.20%, 7.53%, 8.66%, and 8.19%. There is an influence in giving rice diet toward energy, protein, fat and carbohydrates absorbtion of Thypoid patients(p: 0.000, p: 0.006, p: 0.008, p: 0.011) and there is no influence in giving rice diet and porridge diet toward the duration of treatment (p: 0305).Conclusion: Giving rice diet will increase energy, protein, fat and carbohydrates absorption of typhoid patients but doesnot influence the duration of treatment.